COMMUNICATION PATTERNS OF TEACHERS AND AUTISTIC CHILDREN AT THE STAGES OF TEACHING AND LEARNING ACTIVITIES - Yusuf Hartawan; Zahrah Nabila Azka; Fanny Oktaviani; Sharul Chandra (SEAN Institute, 2023)
Based on the background of the communication activities that occur are not only carried out with individuals who are physically and mentally normal, but there is also communication carried out with people who have special needs, especially children who have physical and psychological developmental barriers in communicating. In this study the research team wanted to find out how verbal and nonverbal interpersonal communication was built between teachers and autistic children at the stages of teaching and learning activities so that communication patterns emerged. The theory used is social penetration from Irwin Almant and Dalmas Taylor. While the research method uses case study. The informants in this study were teachers, parents of students and students who were considered to be able to represent interviewees as resource persons.The research results obtained from the development of communication relationships that occur between teachers and children with autism through interpersonal communication at the Orientation stage are carried out gradually as an initial interaction between teachers and children with autism to build mutual trust.